2020
DOI: 10.1039/c9na00780f
|View full text |Cite
|
Sign up to set email alerts
|

Does gold behaves as hydrogen? A joint theoretical and experimental study

Abstract: It has been established that the noble-metal-H analogue has been found in a large number of noble-metalligand clusters in view of geometric and electronic structures. Here, we demonstrated a different view of noblemetal-H analogue between noble-metal and hydrogen in M(SCH 3 ) 2 À (M ¼ Cu, Ag, Au and H) systems. Although H(SCH 3 ) 2 À is a typical ion-hydrogen bonding cluster dramatically different from the chemical bonding clusters of M(SCH 3 ) 2 À (M ¼ Cu, Ag and Au), the comparison of the two typical bonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The Au–H analogy was also verified by the comparable energy gaps between HOMO and the lowest unoccupied molecular orbital (LUMO) and comparable binding energies per atom ( E b ) (Figure a). On the contrary, several reports have claimed that HAu n –1 ( n = 3–8, 20) have a larger adsorption energy of CO and O 2 ( E CO and E O2 , respectively) than those of pristine Au n . , Later work by Ghanty and Banerjee demonstrated that this marked difference in E CO and E O2 is due to the usage of significantly different structures of Au n and HAu n –1 in the estimation . Indeed, the E CO and E O2 values calculated for the most stable Au n and HAu n –1 shown in Figure were very similar except for n = 3 (Figure b and c).…”
Section: Gold–hydrogen Analogy In Naked Gold Superatomsmentioning
confidence: 97%
“…The Au–H analogy was also verified by the comparable energy gaps between HOMO and the lowest unoccupied molecular orbital (LUMO) and comparable binding energies per atom ( E b ) (Figure a). On the contrary, several reports have claimed that HAu n –1 ( n = 3–8, 20) have a larger adsorption energy of CO and O 2 ( E CO and E O2 , respectively) than those of pristine Au n . , Later work by Ghanty and Banerjee demonstrated that this marked difference in E CO and E O2 is due to the usage of significantly different structures of Au n and HAu n –1 in the estimation . Indeed, the E CO and E O2 values calculated for the most stable Au n and HAu n –1 shown in Figure were very similar except for n = 3 (Figure b and c).…”
Section: Gold–hydrogen Analogy In Naked Gold Superatomsmentioning
confidence: 97%
“…[54] They have been investigated for years in AuNC formation since the 1 s electron of hydrogen can mimic the 6 s electron of gold. [55] Hydrides are found to bridge gold [56] as in [Au 22 H 4 (dppo) 6 ] 2 + (Figure 1 H-2) and in some other cases they simply bind a single gold (Figure 1 H-1). [57] Hydrogen bonds between gold and hydrogen in AuNC systems have also been investigated.…”
Section: Ligand Library Of Auncsmentioning
confidence: 99%
“…Hydrogens are not typically considered as functional ligands but they are being more involved in bonding surface metals of metal clusters lately for hydrogenation reactions [54] . They have been investigated for years in AuNC formation since the 1 s electron of hydrogen can mimic the 6 s electron of gold [55] . Hydrides are found to bridge gold [56] as in [Au 22 H 4 (dppo) 6 ] 2+ (Figure 1 H‐2) and in some other cases they simply bind a single gold (Figure 1 H‐1) [57] .…”
Section: Ligand Library Of Auncsmentioning
confidence: 99%